The quiescin sulfhydryl oxidase (hQSOX1b) tunes the expression of resistin-like molecule alpha (RELM-α or mFIZZ1) in a wheat germ cell-free extract. - Wael Gad; Meera G Nair; Karolien Van Belle; Khadija Wahni; Henri De Greve; Jo A Van Ginderachter; Guy Vandenbussche; Yaeta Endo; David Artis; Joris Messens (PLoS ONE, 2013)
Although disulfide bond formation in proteins is one of the most common types of post-translational modifications, the production of recombinant disulfide-rich proteins remains a challenge. The most popular host for recombinant protein production is Escherichia coli, but disulfide-rich proteins are here often misfolded, degraded, or found in inclusion bodies.We optimize an in vitro wheat germ translation system for the expression of an immunological important eukaryotic protein that has to form five disulfide bonds, resistin-like alpha (mFIZZ1). Expression in combination with human quiescin sulfhydryl oxidase (hQSOX1b), the disulfide bond-forming enzyme of the endoplasmic reticulum, results in soluble, intramolecular disulfide bonded, monomeric, and biological active protein. The mFIZZ1 protein clearly suppresses the production of the cytokines IL-5 and IL-13 in mouse splenocytes cultured under Th2 permissive conditions.The quiescin sulfhydryl oxidase hQSOX1b seems to function as a chaperone and oxidase during the oxidative folding. This example for mFIZZ1 should encourage the design of an appropriate thiol/disulfide oxidoreductase-tuned cell free expression system for other challenging disulfide rich proteins.